Fighting the obscene, pornographic, and unhealthy - an analysis of the nature, extent, and regulation of China’s online pornography within a global context - Liang, Bin (Crime, law and social change, 2012)
China’s Internet development has experienced an explosive growth in the last two decades. As China became the largest Internet user in the world, cyber crimes presented a new challenge. In its efforts to combat cyber crimes, the Chinese government singled out online pornography and labeled it "online narcotics." Using the reports of online pornography found in the People’s Daily, a leading national newspaper, this study examines the extent and nature of online pornography in China’s unique context and how the Chinese government has worked to counter such crimes. The analyses of the official reports indicate that the number of China’s porn users has reached millions and continues to grow. To combat such behavior, the Chinese government has adopted a number of countermeasures such as increased law-making, strengthened law enforcement, and the use of new technology. While these countermeasures parallel those of other nations, China’s regulation also presents a number of unique features, such as its broad and sweeping control of online pornographic and unhealthy material for both adults and juveniles, its campaign-style policing, and its emphasis on building consensus with little dissenting opinion. China’s overreaching and proactive approach indicates substantial differences in national standards, value systems, and legal practices between China and many other nations.